Metaverse chronicles: A bibliometric analysis of its evolving landscape - Wider, Walton; Jiang, Leilei; Lin, Jiaming; Muhammad Ashraf, Fauzi; Li, Jingjing; Chan, Choon Kit (Taylor and Francis, 2023)
The Metaverse, a hypothetical virtual space where people interact with digital environments, has gained attention as a transformative concept in various industries like education, healthcare, and business. However, a comprehensive understanding of the Metaverse’s research landscape and future prospects is essential to guide further exploration and decision-making in this dynamic field. On the basis of the preliminary analysis and the existing literature, the comprehensive bibliometric analysis of the Metaverse is anticipated to reveal a number of themes that span the vast spectrum of its applications. The objective of the analysis is to provide a comprehensive overview of the current state and future prospects of the Metaverse by analyzing past and present research trends and predicting future research directions. The research collected 928 journal articles from the Web of Science database using bibliometric methods. Through co-citation and co-word analysis, the study identifies the most influential publications, outlines the knowledge structure, and forecasts future developments. The study identified four distinct clusters for co-citations analysis and five distinct clusters for co-word analysis. Despite the growing importance of the Metaverse in various aspects of human life, more scholarly efforts are required to provide a comprehensive overview of its research landscape. This article provides illuminating insight into the expanding field of Metaverse research and its applications to human life. The study concludes with a comprehensive explanation of Metaverse research and perspectives on the field’s future development. This is the first study to present a knowledge structure of the Metaverse via a science mapping methodology.